Research on static seating comfort of the Chinese population under different seat angle design parameters - Yan, Lingbo; Yu, Lingchun; Li, Na; Shangguan, Luozhe; Luo, Muni (Frontiers in Bioengineering and Biotechnology, 2025)
IntroductionThis study aimed to deepen the understanding of seating comfort for the Chinese population by developing a human finite element (FE) model.MethodsThis model was integrated with a specific vehicle seat FE model to construct a comprehensive human-seat FE model, and the mechanical responses of the human body were analyzed under varying seat angles. Body pressure distribution, intervertebral disc stress and strain, and vertebral body stress were examined to study the relationship between the internal reactions of the human body and surface contact conditions.ResultsThe results indicate that when the seat is flipped, the trends of disc stress, average pressure, and contact area are consistent, and the maximum strain closely aligns with the maximum pressure. When the backrest is adjusted, lumbar spine stress and surface pressure exhibit similar trends, while disc stress, strain, and the 1-SPD value show consistent patterns.DiscussionThe study concludes that increasing the backrest angle does not necessarily enhance comfort. Moreover, the stress variations in the thoracic and lumbar spines correlate with spinal angle alterations, suggesting that spinal angle can serve as a reliable indicator of stress conditions. Finally, the study highlights the correlation between spinal force and body pressure distribution, underscoring the utility of body pressure distribution metrics as a valuable proxy for understanding spinal responses.